PENGARUH PENGETAHUAN AKUNTANSI, PENGHARGAAN FINANSIAL, DAN LINGKUNGAN KERJA TERHADAP MINAT MAHASISWA DALAM PEMILIHAN KARIR MENJADI SEORANG AKUNTAN PUBLIK - Ayu Cahyaningrum; Hadi Samanto; Suhesti Ningsih (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This research aims to determine the influence of accounting knowledge, financial rewards, and work environment on students' interest in choosing a career as a public accountant. This research is quantitative research with a population of Soloraya accounting students, samples were taken using the Slovin formula from 100 respondent. Data analysis uses multiple linear regression models, hypothesis testing and classic assumption tests consisting of normality tests, multicollinearity tests and autocorrelation tests. The research results show that the feasibility test of the model on accounting knowledge, financial rewards and work environment influences students' interest in becoming public accountants. Which means this regression model is suitable for use. This is proven by the F test, which obtained a significance of 0.005 < α = 0.05. The results of the partial t test show that accounting knowledge, financial rewards and the work environment influence students' interest in becoming public accountants with a significance value of <0.05. The Adjust R Square value is 68.6%, which means 68.6%, which means the independent variable (accounting knowledge, financial rewards and work environment) has an influence of 68.6% on the dependent variable (interest in becoming a public accountant).